Pengaruh Current Ratio, Total Asset Turnover, Debt To Equity Ratio, Net Profit Margin Terhadap Roa Pada Perusahaan Property & Real Estate Yang Terdaftar Di BEI Tahun 2019 - 2021 - Mahmuddin Syah Lubis; Arman Osvaldo Siburian; Rivaldo Cokro; Yusneni Afrita Nasution (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The study aims to determine the effect of Curent Ratio, Total Asset Turnover, Debt to Equity Ratio, Net Profit Margin on ROA in property and real estate companies listed on the IDX in 2019 - 2021. Quantitative descriptive research method, collecting data using research instruments and statistically analyzed in testing hypotheses. The population was 80 companies in the field of property and real estate, a sample of 20 companies with purposive sampling technique. The results of the study found that Current Ratio is partially significant to the company's Return on Assets with a tcount of Current Ratio 0.557, ttable 2.000 (tcount < ttable) and its significance is 0.580, which is> 0.05. Total Assets Turnover partially affects the company's Return on Assets with a tcount of Total Assets Turnover 2.909, ttable 2.000 (tcount> ttable) and its significance is 0.005, namely <0.05. Debt to Equity Ratio is not significant to the company's Return on Assets worth thitung Debt to Equity Ratio 1.131, ttabel 2.000 (titung < ttabel) significance 0.268 which is> 0.05 Net Profit Margin partially affects the company's Return on Assets worth thitung Net Profit Margin 10. 509, ttable 2,000 (tcount> ttable), the significance is 0.000 which is <0.05.Current Ratio, Total Asset Turnover, Debt to Equity Ratio and Net Profit Margin are significant to Return on Asset worth Fhitung> Ftabel (29,548> 2,536). Keywords: Current ratio, total asset turnover, debt to equity ratio, net profit margin ratio and return on assets.